2021
DOI: 10.1166/jnn.2021.18513
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Structure and Fractal Characteristics of Nanopores in High-Rank Coal: Implications for the Methane Adsorption Capacity

Abstract: The structure and fractal characteristics of nanopores of high-rank coal were investigated using an approach that integrates N2 adsorption and field emission scanning electron microscopy (FE-SEM). The results indicated that the high-rank coal of the Shanxi Formation has a complex pore-fracture network composed of organic matter pores, mineral-related pores, and microfractures. The pore type of high-rank coal tends to be complicated, and the main pore types are inkbottle pores and open pores, which are more co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The characterization methods of pore/fracture structures are summarized as follows: (1) pore size distribution: CO 2 /N 2 adsorption method and mercury injection method; , (2) 2D morphology observation: optical microscopy and scanning electron microscopy; , (3) 3D imaging analysis: X-ray computed tomography (i.e., CT), focused ion beam scanning electron microscopy (i.e., FIB-SEM). , As a nondestructive and high resolution scanning technology, 3D imaging scanning is the most direct and accurate method to reconstruct the pore/fracture structure, which can realize the extraction and reconstruction of interconnected pores/fractures and the analysis of characteristic parameters of geometric and topological structures. , FIB-SEM can only analyze the nanoscale structures; the testing cost is high, and the testing period is long. Therefore, X-ray CT technology can be used to quantitatively analyze the pore/fracture structures and its characteristic parameters of the coal reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…The characterization methods of pore/fracture structures are summarized as follows: (1) pore size distribution: CO 2 /N 2 adsorption method and mercury injection method; , (2) 2D morphology observation: optical microscopy and scanning electron microscopy; , (3) 3D imaging analysis: X-ray computed tomography (i.e., CT), focused ion beam scanning electron microscopy (i.e., FIB-SEM). , As a nondestructive and high resolution scanning technology, 3D imaging scanning is the most direct and accurate method to reconstruct the pore/fracture structure, which can realize the extraction and reconstruction of interconnected pores/fractures and the analysis of characteristic parameters of geometric and topological structures. , FIB-SEM can only analyze the nanoscale structures; the testing cost is high, and the testing period is long. Therefore, X-ray CT technology can be used to quantitatively analyze the pore/fracture structures and its characteristic parameters of the coal reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al revealed the structure and fractal characteristics of micropores and mesopores in low- and middle-rank tectonic-deformed coals by combining the absorption experiment and fractal theory. Subsequently, several scholars have also demonstrated that the fractal dimension affects porosity, gas adsorption capacity, and permeability. , …”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, several scholars have also demonstrated that the fractal dimension affects porosity, gas adsorption capacity, and permeability. 26,27 To sum up, great progress has been achieved in the area of coal pore characterization. 16,27,28 However, the relatively high micropore content of coal is the main place of gas occurrence, and studies applying the fractal theory to microporosity have rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation